PENGEMBANGAN MEDIA PAPIMAG (PAPAN PINTAR MAGNETIK) PADA MATERI SIMBOL RAMBU LALU LINTAS KELAS 3 SEKOLAH DASAR - Dwi Retno Suharyani; Nanang Khoirul Umam; Arya Setya Nugroho (Nusantara Hasana Journal, 2023)
This study aims to describe the development process and quality of papimag media on the material of symbols and traffic sign symbols for grade 3 elementary school students. The research is the ADDIE (The initial stage of analysis is performance analysis that can be done to find out the problems that are being faced in the classroom. Design designing or compiling a media creation framework from media design, material. Development develops learning media based on the initial design. Implementation conducts media trials in the learning process. Evaluation at this stage a final revision of the developed media is carried out). The subjects in this study were students of grade 3 UPT SD Negeri 131 Gresik, totaling 18 students. The learning model used during implementation uses 3 models, the first is Teams Group Tournament, Inquiry Based Learning, and Group Discussion. Data collection techniques in this study were using validation sheets and student questionnaires. Analysis of the data obtained from the validation sheet of the media expert in the graphic aspect obtained a percentage of 90% and the linguistic aspect obtained a percentage of 91.6%, while the validation of the material expert on the presentation aspect obtained a percentage of 75% and the content feasibility aspect obtained a percentage of 100% with the criteria of "very good".